Association of serum ferritin with insulin resistance, abdominal obesity, and metabolic syndrome in Korean adolescent and adults: The Korean National Health and Nutrition Examination Survey, 2008 to 2011. Issue 8 (February 2017) - Shim, Young Suk; Kang, Min Jae; Oh, Yeon Jeong; Baek, Joon Woo; Yang, Seung; Hwang, Il Tae
Abstract : Abstract: This study aimed to evaluate the associations of serum ferritin with insulin resistance indices, body fat mass/percentage, and all the components of metabolic syndrome (MetS), as well as the risk for MetS according to serum ferritin levels in Korean adolescents and adults. A total of 15, 963 Korean males and females aged 16 to 80 years were analyzed using data from the Korean National Health and Nutrition Examination Survey, 2005 to 2011. The median serum ferritin concentration was 98.82 ng/mL for males and 38.60 ng/mL for females ( P < 0.001). Increased risks of greater waist circumference and elevated glucose levels, elevated triglyceride levels, and reduced high-density lipoprotein cholesterol levels were noted across the serum ferritin quartiles after adjustment for confounders in both genders ( P ⩽ 0.012 for trend). Insulin resistance indices and abdominal obesity (trunk fat mass/percent) increased across the ferritin concentration quartiles after adjustment for confounders in males and females ( P ⩽ 0.011 for trend), and the risk of MetS increased across the ferritin quartiles in males ( P < 0.001 for trend) and females ( P = 0.001 for trend). The highest serum ferritin quartile exhibited a 1.62-fold increased risk of MetS (95% CI, 1.28–2.12) in males and a 1.36-fold increased risk of MetS (95% CI, 1.09–1.69) in females compared with the lowest quartile after adjustment for confounders. Our results suggest that ferritin is associated with insulin resistance and abdominal obesity.